Industry and the urge to cluster: A study of the informal sector in India - Megha Mukim (European Regional Science Association (ERSA), 2010)
The distribution of economic activity over physical space - economic geography - is central to economic development. Geographical variations in industrialisation are the primary factor affecting geographical variations in incomes. And so, the question of what drives industry to locate in one region and not in the next is vital to an understanding of economic growth and development. Policy-makers trying to encourage economic activity to locate in regions it has not previously favoured want answers - is it a set of infrastructure? Fiscal incentives? Good business environment? Or could it be agglomeration - the compounding effect of existing industry? The primary objective of this research is to investigate the extent to which agglomeration economies affect the location decisions of firms. The paper will study the specific case of firms in the services industry - precisely, how and why they have chosen to locate themselves across India. It does this by using an econometric model of industrial location to estimate the determinants of location choice by services firms in India by using data on close to 5000 companies across 7 service sub-sectors over 20 years and 170 locations. Measures of total factor productivity are generated by estimating production functions using plant-level physical output data. The Levinsohn and Petrin (2003) method is exercised and intermediate inputs control for the simultaneity problem. The paper carries out an empirical exercise to explain individual firm's decisions, based on their levels of productivity, as a function of observable location-specific advantages, economic geography factors, such as market access and agglomeration economies, and a set of unobserved local attributes. Endogeneity concerns are dealt with using the Instrumental Variable approach. In theory, if government is interested in encouraging firms to locate in particular regions, it should have a clear understanding of what factors drive industry location decisions.
Keywords: R12; R3; O17; 330